Mycoplasma pneumoniae pneumonia-associated thromboembolism with plastic bronchitis: a series of five case reports and literature review - Peng Jin; Chunjiao Han; Wei Guo; Yongsheng Xu (Italian Journal of Pediatrics, 2024)
Abstract Background Mycoplasma pneumoniae pneumonia is a common respiratory infection among children. However, the occurrence of thromboembolism with plastic bronchitis in association with Mycoplasma pneumoniae pneumonia is extremely rare. This case series presents five cases of children with Mycoplasma pneumoniae pneumonia who developed thromboembolism and plastic bronchitis. The clinical presentation, diagnostic approach, and management strategies are discussed. Methods A retrospective analysis was conducted on medical records from a pediatric hospital. Patient demographics, clinical features, laboratory findings, imaging results, treatment modalities, and outcomes were collected. Results The patients in our case series presented with varying degrees of respiratory distress, cough, and fever. Imaging studies revealed evidence of thromboembolism based on pulmonary artery occlusion. Bronchial casts were observed by bronchoscopy. Laboratory tests demonstrated elevated D-dimer levels and fibrinogen degradation products. All patients received a combination of low molecular weight heparin anticoagulation and supportive care. Conclusion Thromboembolism with plastic bronchitis associated with Mycoplasma pneumoniae pneumonia is a rare but potentially serious complication in children. Prompt recognition and management are crucial for improving patient outcomes. This case series highlights the diverse clinical presentations, diagnostic challenges, and treatment strategies for this unique clinical entity. Further research is needed to better understand the pathogenesis and optimal management of this condition.